Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1038/srep30169
|View full text |Cite
|
Sign up to set email alerts
|

Cranberry-derived proanthocyanidins impair virulence and inhibit quorum sensing of Pseudomonas aeruginosa

Abstract: Bacteria have evolved multiple strategies for causing infections that include producing virulence factors, undertaking motility, developing biofilms, and invading host cells. N-acylhomoserine lactone (AHL)-mediated quorum sensing (QS) tightly regulates the expression of multiple virulence factors in the opportunistic pathogenic bacterium Pseudomonas aeruginosa. Thus, inhibiting QS could lead to health benefits. In this study, we demonstrate an anti-virulence activity of a cranberry extract rich in proanthocyan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 99 publications
(57 citation statements)
references
References 78 publications
2
50
0
1
Order By: Relevance
“…Such characteristics have been previously reported for extracts from other berry fruits, including cranberry and blueberry (Ben Lagha, Groeger, et al, ; Ben Lagha et al, ; Feldman et al, ; Feghali et al, ). Although we did not investigate the antibiofilm mechanism of the tart cherry fractions, it may be related to their ability to modify the microbial cell surface hydrophobicity, to inhibit the gene expression of adhesins, or to interfere with the quorum sensing, as previously reported for cranberry extracts (Maisuria, Lopez‐de Los Santos, Tufenkji, & Déziel, ; Rafsanjany, Senker, Brandt, Dobrindt, & Hensel, ; Yamanaka, Kimizuka, Kato, & Okuda, ).…”
Section: Discussionmentioning
confidence: 96%
“…Such characteristics have been previously reported for extracts from other berry fruits, including cranberry and blueberry (Ben Lagha, Groeger, et al, ; Ben Lagha et al, ; Feldman et al, ; Feghali et al, ). Although we did not investigate the antibiofilm mechanism of the tart cherry fractions, it may be related to their ability to modify the microbial cell surface hydrophobicity, to inhibit the gene expression of adhesins, or to interfere with the quorum sensing, as previously reported for cranberry extracts (Maisuria, Lopez‐de Los Santos, Tufenkji, & Déziel, ; Rafsanjany, Senker, Brandt, Dobrindt, & Hensel, ; Yamanaka, Kimizuka, Kato, & Okuda, ).…”
Section: Discussionmentioning
confidence: 96%
“…It is previously reported that the SIC of antimicrobials modulates the expression of various virulence proteins and associated genes in bacteria thereby resulting in changes in their pathophysiology and virulence (Goh et al, 2002; Tsui et al, 2004; Qiu et al, 2010; Upadhyay et al, 2012, 2014; Maisuria et al, 2016). To study if similar mechanisms exist in Campylobacter , we investigated the effect of BR on various genes of Campylobacter that are known to facilitate colonization in poultry.…”
Section: Discussionmentioning
confidence: 99%
“…cPAC was an effective potentiator against diverse bacterial lifestyles normally tolerant to antibiotics, such as biofilm bacteria, dormant cells, and in experimental models of chronic infections. [19] Studies suggest that consumption of cranberry Antibiotic resistance is spreading at an alarming rate among pathogenic bacteria in both medicine and agriculture. These results suggest that in combination with antibiotic therapy, cPAC has the potential to decrease the spread of antibiotic resistance and prolong the effectiveness of currently available drugs.…”
mentioning
confidence: 99%